Enterococcus faecalis AHG0090 is a Genetically Tractable Bacterium and Produces a Secreted Peptidic Bioactive that Suppresses Nuclear Factor Kappa B Activation in Human Gut Epithelial Cells - Ó Cuív, Páraic; Giri, Rabina; Hoedt, Emily C.; McGuckin, Michael A.; Begun, Jakob; Morrison, Mark (Frontiers in Immunology, 2018)
Enterococcus faecalis is an early coloniser of the human infant gut and contributes to the development of intestinal immunity. To better understand the functional capacity of E. faecalis we constructed a broad host range RP4 mobilisable vector, pEHR513112, that confers chloramphenicol resistance and used a metaparental mating approach to isolate E. faecalis AHG0090 from a faecal sample collected from a healthy human infant. We demonstrated that E. faecalis AHG0090 is genetically tractable and could be manipulated using traditional molecular microbiology approaches. E. faecalis AHG0090 was comparable to the gold-standard anti-inflammatory bacterium Faecalibacterium prausnitzii A2-165 in its ability to suppress cytokine mediated NF-B activation in human gut derived LS174T goblet cell-like and Caco-2 enterocyte-like cell lines. E. faecalis AHG0090 and F. prausnitzii A2-165 produced secreted low molecular weight NF-B suppressive peptidic bioactives. Both bioactives were sensitive to heat and proteinase K treatments although the E. faecalis AHG0090 bioactive was more resilient to both forms of treatment. As expected, E. faecalis AHG0090 suppressed IL-1 induced NF-B-p65 subunit nuclear translocation and expression of the NF-B regulated genes IL-6, IL-8 and CXCL-10. Finally, we determined that E. faecalis AHG0090 is distantly related to other commensal strains and likely encodes niche factors that support effective colonisation of the infant gut.